Why a Different Approach to Science Teaching - Dewan, Hriday Kant (Voices of Teachers and Teacher Educators, 2018)
The paper explores different approaches to science teaching and shares an analysis of reflection of the idea of quality science education in the policy and curricular documents. It also presents and analyses some experiences of working with teachers and the implications if that. The notion of the meaning of good science education has been a contentious debate. The understanding of good science-education has evolved over time in the context of Indian education. Over the last few decades experiments have become an important component of science education in schools. The manner of its articulation and its expression in the materials and methods does not reflect the spirit of understanding of either the notion of science or the possible purpose and the process of learning science. It is not that there are no known efforts from India in this direction and no alternative examples and principles available. But the principles in the policy and the curricular documents and even from the Hoshangabad science education program have been reduced to a few catchwords and rituals. The understanding of science education must consider the nature of science including the meaning and purpose of education. It must also consider its relationship with society including the concern about its hegemonic relationship in some world views. The purpose and the methods apart from all this must also include in some manner the experience and abilities of children. While this is not easy to construct in a simple meaningful manner, the principles can be articulated but their exposition in the classrooms depends on the beliefs and confidence in teachers. Teachers even though enjoying an exploratory experience of experiments and analysis with simple components of generalisation do not feel confident of being able to make such experiences possible for children in the classrooms.